Monitoring topographic changes in a periglacial high‐mountain face using high‐resolution DTMs, Monte Rosa East Face, Italian Alps - Luzia Fischer; Henri Eisenbeiss; Andreas Kääb; Christian Huggel; Wilfried Haeberli (Permafrost and Periglacial Processes)
This paper describes a remote sensing‐based approach for detailed topographic investigations in steep periglacial high‐mountain faces. The study was conducted at one of the highest periglacial rock faces in the European Alps, the permafrost‐affected and partially glacierised east face of Monte Rosa. Strongly increased rock and ice avalanche activity on this rock wall has caused major topographic change in recent decades. A time series of high‐resolution digital terrain models (DTMs) with a 2‐m resolution was produced from digital aerial photogrammetry for 1956, 1988 and 2001 and from airborne LiDAR for 2005 and 2007. The DTM comparisons reveal a total volume loss of permafrost‐affected bedrock and glacier ice of more than 20 × 106 m3 over the past 50 years, with the majority of the loss since 1988. Analysis of all unstable areas and detachment zones showed that the sequence of the main slope failures is spatially connected and that there is coupling between permafrost bedrock instability and the condition of adjacent hanging glaciers. Copyright © 2011 John Wiley & Sons, Ltd.